METODE ACTIVITY BASED COSTING (ABC) DALAM PERHITUNGAN TARIF KAMAR RAWAT INAP - Perdana, Wildan Muhammad (Media Akuntansi dan Perpajakan Indonesia, 2020)
This study is conducted on the basis of the development of businesses that lead to higher levels of business competition. Hospital is a nonprofit institution, and therefore the required accuracy of the management in making decisions, especially in determining inpatient room rates to maintain the viability of the hospital. Activity based costing is considered to provide more accurate than the traditional method for calculating the basic rate of hospitalization, so as to assist the management in setting room rates of hospitalization that can be adapted to the resources used by each class. In this study, drivers used in the calculation of rates of hospitalization is, the number of days of hospitalization, the number of inpatients, electric power consumption (KWH), and room areas. The results showed that the calculation of the difference in activity based costing are high on the room type with second class and third class.